2020
DOI: 10.1021/jacs.0c04964
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Unusual Ability of the [FeFe] Hydrogenase from Clostridium beijerinckii to Access an O2-Protected State

Abstract: [FeFe] hydrogenases are enzymes capable of producing and oxidizing H2 at staggering submillisecond time scales. A major limitation in applying these enzymes for industrial hydrogen production is their irreversible inactivation by oxygen. Recently, an [FeFe] hydrogenase from Clostridium beijerinckii (CbHydA1) was reported to regain its catalytic activity after exposure to oxygen. In this report, we have determined that artificially matured CbHydA1 is indeed oxygen tolerant in the absence of reducing agents and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 49 publications
14
49
0
Order By: Relevance
“…3 and 5). This observation is consistent with a recently published hypothesis according to which the loop that bears C367 in CbA5H may be flexible enough to allow the binding of the cysteine to Fe d 31 . The strictly conserved cysteine residue is involved in long-range proton transfer to and from the H-cluster (Supplementary Figure 6) 4,16,18 .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…3 and 5). This observation is consistent with a recently published hypothesis according to which the loop that bears C367 in CbA5H may be flexible enough to allow the binding of the cysteine to Fe d 31 . The strictly conserved cysteine residue is involved in long-range proton transfer to and from the H-cluster (Supplementary Figure 6) 4,16,18 .…”
Section: Resultssupporting
confidence: 93%
“…However, DdH becomes O 2 -sensitive after gaining catalytic activity 10,19 . For DdH and some other [FeFe]-hydrogenases, sulfide-addition under oxidizing conditions (either aerobic or anaerobic) also produces the H inact -state; the anaerobic formation of H inact is detected in cyclic voltammetry by the early onset of oxidative inactivation 30,31 . Rodríguez-Maciá et al concluded that H inactformation under oxidizing conditions is the consequence of sulfide-binding to Fe d 30 , but this protected state is also formed in CbA5H 27,31 and CpIII ([FeFe]-hydrogenase III from Clostridium pasteurianum) 32 in the absence of exogenous sulfide.…”
Section: [Fementioning
confidence: 99%
See 1 more Smart Citation
“…29 Following the development of a computational methodology for an accurate prediction of the IR spectra of the active site of [FeFe]-hydrogenase, 256 many studies have been conducted using DFT calculations and helped in the unambiguous assignment of the structure and redox states of intermediates like for the H-cluster. [257][258][259][260] While the calculated absolute vibrational frequencies are often not quantitatively accurate, shifts in frequencies due to protonation and/or reduction events are reliable. Due to the peculiar vibrational frequencies of the CN and CO groups, it is possible to distinguish the redox states of the [NiFe] active site.…”
Section: Spectroscopic Propertiesmentioning
confidence: 99%
“…For a long time, the major drawback of [FeFe] hydrogenases was their oxygen sensitivity [8][9][10]. However, methods that have recently been identified can protect these enzymes for later use [11][12][13][14], and even enzymes with a self-protection mechanism have been discovered [15,16].…”
Section: Introductionmentioning
confidence: 99%